AI Adoption for Tax Consultant Productivity: Validity and Reliability of Instruments - Novia Rahmadina; Mutmainnah (www.amertainstitute.com, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on tax consulting practices in Indonesia. This study aims to develop and test the validity and reliability of instruments used to measure AI adoption and tax consultant productivity. In addition, this study also considers digital literacy as a moderating variable that has the potential to influence the relationship between AI adoption and productivity. A quantitative approach was used by distributing questionnaires to 217 Indonesian Tax Consultants Association (IKPI) tax consultants. AI adoption was measured using the General Attitudes Toward Artificial Intelligence Scale (GAAIS) model, while productivity and digital literacy were measured based on indicators relevant to the professional work context. The analysis results show that all items in the instrument meet the construct validity criteria through Pearson correlation tests and internal reliability with Cronbach's Alpha values above 0.8 for all three constructs. These findings confirm that the developed instrument is suitable for use in further studies related to AI adoption in the tax consultant work environment. This study contributes methodologically to measuring technology adoption in the professional sector and has practical relevance for professional organizations, educational institutions, and policymakers in designing data-driven interventions. The confirmed validity and reliability also strengthen the basis for decision-making in enhancing the competencies of tax consultants to address the challenges of the digital era.